Design and Characterization of Twisted and Coiled Polymers and Their Applications as Soft Actuators - Martin, Jacob (Université d'Ottawa / University of Ottawa, 2023)
Current progress in mobility assistive devices revolves around traditional actuation methods including electric motors, hydraulics, and pneumatic cylinders to provide assistive joint torques to the user. While these mechanisms are effective at providing the torques needed, they are often bulky, heavy, and suffer from poor alignment with the joints of the user. These drawbacks have created a need for novel technologies that can provide a more compact and compliant form of actuation. Twisted and coiled polymers, under the thermomechanical class of smart material actuators, have emerged as a strong candidate for use as soft actuators in assistive devices due to their low cost, commercial availability, high stroke capacity, and power density. Progress to their development is currently limited by lack of proper standardization in the fabrication process, along with incomplete characterization of its quasi-static mechanical and thermal behaviours and how the performance is influenced by various design considerations. This thesis defined a fabrication process of twisted coiled polymer actuators and evaluated the trends between design considerations and their impacts on the final actuator performance. In this work, a fabrication rig was developed to manufacture consistent and repeatable actuators, while enabling the control of various identified design parameters. Subsequently, a comprehensive experimental evaluation was accomplished which resulted in a better understanding of the relationships between these parameters and the actuator performance including its tensile stroke, force generation, and variable stiffness properties. The results provided a foundation for designers to consider which variables should be controlled during both actuator fabrication and operation, in order to optimize its final performance to meet a set of prescribed requirements.
Keywords: Twisted Coiled Polymers; TCP; Soft Actuator; Variable Stiffness; Artificial Muscle; Smart Materials